PENGARUH SOSIALISASI PERPAJAKAN, PENGETAHUAN PERPAJAKAN, PERSEPSI WAJIB PAJAK TENTANG SANKSI PAJAK DAN IMPLEMENTASI PP NOMOR 46 TAHUN 2013 TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI ( Studi Empiris pada Wajib Pajak di Kabupaten Banjarnegara ) - Hana Pratiwi Burhan; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2015)
This study aimed to analyze the factors that affect an individual taxpayer compliance in Banjarnegara.  This  study  consists  of  four  independent  variables  and  the  dependent variable. independent variable in this study is the socialization of taxation, tax knowledge, perceptions taxpayer about tax penalties and taxpayers perception on the implementation of PP 46 tahun2013. While the dependent variable in this study is the individual taxpayer compliance.This study used a simple random sampling technique and using the questionnaire survey method  in  data  collection,  respondents  were  sampled  individual  taxpayers  who  are enrolled in KP2KP Banjarnegara. Research data analysis using multiple regression analysis with SPSS 16.0.Based  on  the analysis  that  has  been  done,  this  study  shows  that the socialization  of taxation,  tax  knowledge,  and  perceptions  of  the  taxpayer  of  PP  46  in  2013  and  a significant positive effect on the individual taxpayer compliance. While the taxpayer perceptions about tax penalties do not affect the compliance of individual taxpayers.